Perspectives and New Aspects of Metalloproteinases’ Inhibitors in the Therapy of CNS Disorders: From Chemistry to Medicine - Boguszewska-Czubara, Anna; Budzynska, Barbara; Skalicka-Wozniak, Krystyna; Kurzepa, Jacek (Current Medicinal Chemistry, 2019)
Matrix metalloproteinases (MMPs) play a key role in remodeling of the extracellular matrix (ECM) and, at the same time, influence cell differentiation, migration, proliferation, and survival. Their importance in a variety of human diseases including cancer, rheumatoid arthritis, pulmonary emphysema and fibrotic disorders has been known for many years but special attention should be paid on the role of MMPs in the central nervous system (CNS) disorders. Till now, there are not many well documented physiological MMP target proteins in the brain but only some pathological ones. Numerous neurodegenerative diseases are a consequence of or result in disturbed remodeling of brain ECM, therefore proper action of MMPs as well as control of their activity may play crucial roles in the development of these diseases. In the present review, we discuss the role of metalloproteinase inhibitors, from the wellknown natural endogenous tissue inhibitors of metalloproteinases (TIMPs) to the exogenous synthetic ones like (4-phenoxyphenylsulfonyl)methylthiirane (SB-3CT), tetracyclines, batimastat (BB-94) and FN-439. As the MMP-TIMP system has been well described in physiological development as well as in pathological conditions mainly in neoplastic diseases, the knowledge about the enzymatic system in mammalian brain tissue still remains poorly understood in this context. Therefore, we focus on MMPs inhibition in the context of the physiological function of the adult brain as well as pathological conditions including neurodegenerative diseases, brain injuries, and others.
Keywords: brain